The legal consequences of errors in the determination of heirs in the perspective of the compilation of Islamic law (A study of decision no. 0417/Pdt.P/2022/PA.Mlg) - Amin Songgirin (Priviet Social Sciences Journal, 2025)
This study aims to analyze the errors in the determination of heirs in the Religious Court of Malang Decision Number 0417/Pdt. P/2022/PA.Mlg and examine its legal consequences based on the Compilation of Islamic Law (KHI) in Indonesia. This study employs a normative juridical approach by reviewing the provisions of Article 185 of the KHI, various schools of Islamic jurisprudence (madzhab), and Gustav Radbruch’s theory of justice as analytical tools. The findings reveal that the judge’s determination, which classified Applicants II, III, and IV as dzawil arham, constitutes a misjudgment because, normatively, they are entitled to inheritance as substitute heirs. This error leads to legal consequences in the form of the loss of inheritance rights that should have been granted to the descendants of the testator’s sister, potentially creating legal uncertainty and further disputes. From the perspective of fiqh, although the Syafi’ i school rejects the concept of substitute heirs, the Hanafi and Maliki schools recognize the transmission of inheritance rights through both vertical and collateral lines of descent. The KHI accommodates the latter view to realize substantive justice within Islamic inheritance law in Indonesia. This study underscores the necessity of progressive legal reasoning (rechtsvinding) that aligns with maqāṣid al-sharī‘ah, so that judicial decisions are not merely textually grounded but also reflect the values of justice and social welfare.